Evaluating luteinizing hormone receptor signaling using the cyclic AMP reporter ICUE3 - Hadhoud, Giuma E., author; Roess, Deborah A., advisor; Barisas, George, advisor; Crans, Debbie C., committee member (Colorado State University. Libraries, 2018)
The luteinizing hormone (LH) receptor is a member of the G protein-coupled receptor family and the subfamily of glycoprotein hormone receptors. The LH receptor plays a vital role in normal development and in the function of the gonads. The LH receptor is expressed in interstitial cells, thecal cells, and granulosa cells and in cells making up the corpus luteum. Signal transduction by LH receptors is dependent on hormone activation of LH receptors and subsequent activation of G proteins. Evaluating the cyclic adenosine monophosphate (cAMP) level in response to binding of ligand to LH receptors depends on activation of adenylyl cyclase by G proteins and production of cAMP. In this project, fluorescence resonance energy transfer (FRET) methods were used to evaluate cAMP levels in individual cells in response to binding of ligand to LH receptors. These studies used ICUE3, an EPAC-based reporter molecule for cAMP in cells. ICUE3 is an engineered molecule that contains a FRET donor and acceptor pair as well as a membrane-targeting sequence. FRET occurs when the donor fluorophore in an excited electronic state transfers its excitation energy to a nearby acceptor chromophore. In the absence of bound cAMP, the fluorescence donor in ICUE3 transfers energy to the fluorescence acceptor. When ICUE3 binds cAMP, the donor-acceptor distance increases and the FRET signal is reduced. cAMP levels were evaluated in individual cells expressing ICUE3 and LH receptor under different conditions including exposure of cells to human chorionic gonadotropin (hCG). In some experiments, CHO cells co-expressing ICUE3 and constitutively-active LH receptors, LH receptors yoked to a single-chain modified form of hCG (yLHR), were used to determine whether the presence of a constitutively-active receptor increased basal cAMP levels in CHO cells. Our results show that ICUE3 is a reliable reporter molecule that measures basal cAMP levels in untreated cells and is responsive to changes in intracellular cAMP levels in response to forskolin treatment or, in the presence of a functioning LH receptor, to hCG.
Keywords: cyan fluorescent protein; adenylyl cyclase; cyclic adenosine monophosphate